Discrepancies between the self-reporting of STI preventive care and the actual care provided by male doctors to male patients in Karnataka, India. Issue 5 (3rd August 2010) - Mignone, Javier; Washington, Reynold; Ramesh, B M; Blanchard, James F; Rajaretnam, T; Moses, Stephen
Abstract : Objective: To examine the discrepancies between the self-reporting of STI preventive care and the actual care provided by male doctors to male patients in several subdistricts of the state of Karnataka, south India. Methods: Of 3376 allopathic medical practitioners (doctors) enumerated, 2846 were contacted in person. Doctors who saw at least five patients with STI a month were then interviewed (814). Further, 451 of these practitioners were visited by a 'surrogate patient.' Comparative analyses were conducted of items from the survey questionnaire and from the surrogate patient answer sheet that unambiguously tapped into the same information. Results: Systematic differences in the self-report by the doctors and the report by the surrogate patients were found. For instance, 99% of practitioners reported examining the patients, whereas only 71% of surrogate patients reported being examined. 96% of practitioners reported advising condom use, whereas only 19% of surrogate patients reported receiving this advice. 97% of practitioners reported advising partner treatment, whereas only 10% of surrogate patients reported receiving this advice. Younger practitioners, doctors in rural centres and doctors with STI in-service training were more likely to be discordant in what they self-reported and what surrogate patients reported. Conclusions: The discrepancies between doctor self-reporting and surrogate patient observations bring into question the reliability of practitioner recall, suggesting that the use of self-reporting surveys should be reassessed.